A patient-centred approach to measuring quality in kidney care: patient-reported outcome measures and patient-reported experience measures. Issue 6 (November 2017) - Aiyegbusi, Olalekan L.; Kyte, Derek; Cockwell, Paul; Anderson, Nicola; Calvert, Melanie
Abstract : Purpose of review: Chronic kidney disease (CKD) is associated with symptoms that can significantly reduce the health-related quality of life (HRQOL) of patients. Patient-reported outcome and experience measures (PROMs and PREMs) may assist with the evaluation of HRQOL and quality of care from the patient perspective. This review focuses on evidence from recent studies exploring the role of PROMs and PREMs in the measurement of quality in CKD care. Recent findings: PROMs are increasingly used in CKD research as measures of clinical effectiveness, whereas the current use of PROMs in routine clinical settings and PREMs in all settings is more limited. Electronic PROMs may be sensitive enough to detect clinically relevant patient-reported outcomes changes. Patients on frequent shorter-hours daily haemodialysis may experience better HRQOL compared with those on conventional haemodialysis. PROM data may correlate significantly with clinical parameters. PREMs are being utilized by healthcare professionals to inform service improvements. Summary: PROMs and PREMs may facilitate the measurement of quality in renal care and aid the tailoring of care to individual patients. PROMs may have a potential role as prognostic markers.